SATIATION AND DIGESTION RATE OF MANGROVE SNAPPER FINGERLING (Lutjanus argentimaculatus) - Made Suastika; Philip Teguh Imanto (Indonesian Aquaculture Journal, 2007)
Mangrove snapper is an economically value in domestic as well overseas market, but supplies are mostly sourced from the wild. Observations on satiation and digestion rate of fingerlings was undertaken to provide basic information for culturing mangrove snapper. Ten fingerling mangrove snapper (body weight 3.8—19.5 g) were stocked into each of nine plastic 200 L tanks. After starvation for 24 hours, fish were fed with chopped ‘trash’ fish and the amount of eaten feed was record as satiation data. Feeding data was recorded after 4 hours feeding. The satiation rate for juvenile mangrove snapper followed the power regression line Y=0.4503x-0.6472. Thus, in larger juveniles the satiation rate was lower. Digestion rate followed a polynomial regression line, indicating that digestive activity was not the same during observation time, and analysis of two linear regressions shown that the flection point for digestion rate occurring after 10 hours when digestion rate reached 72%. These results indicate that the optimum feeding rate for mangrove snapper fingerling was 72% of satiation, and optimum feeding frequency two times per day.